(untitled) (Al-Academy, 2021)
The research presents a case study of collecting materials and raw materials in a visual space that allows them to form a perception and meanings that inform the recipient by reconstructing them and inserting them into the surface of the artistic work and in such a way that the aesthetic act consists of a variety of media, touches and surfaces. The overlap of races within an environment characterized by unity. That is why the researcher in chapter one presented the problem of research, and the focus was on studying the multiplicity of materials and their aesthetic and functional role in the structure of creative work. The aim of the research is enhanced to identify the aesthetic performance function of the multiplicity of ores in the collective art, while in chapter two it is the theoretical framework. The researcher divided it into two topics the first entitled (Collective Art, features and Characteristics), and second topic (Collective Art and the interference of races), where the role of raw materials in art and the context of their presence was studied, and then the creative experiences of collegial art in art schools were traced to the stage of modernity and its features were revealed, after which the researcher presented trends and methods of postmodernity, and in it the researcher presented a study of artistic experiences through the overlap between races and aesthetic proposals, so that the artistic work is a vast space for meanings and purposes, while in chapter three he presented to it the title of openness of visual presentation and the multiplicity of raw materials in collective art, then the functional and aesthetic dimension of the multiplicity of materials in collective art and the study of methods and the diversity of use and purposes.that justified this and revealed the type of material and the role of touch person in condensing the given form and visualization techniques As for chapter four , the researcher reached the results in which the visual surface in collective art acquired the element of excitement and surprise through the diversity of materials, their touches and their mediating, and what this presented a state of experimentation and openness of the visual presentation and the employment of neglected and marginalized materials and naturalized materials within the field of drawing or sculpture, but integration techniques and materials after that the researcher made recommendations and suggestions.